Evaluasi Pengendalian Kualitas Kain Grey pada Divisi Weaving Rapier PT XYZ dengan Metode Seven Tools - Faisal Ibrahim; Hanif Awandani; Fariza Halidatsani Azhra (OPSI, 2020)
PT. XYZ is a manufacturing company that produces grey fabrics, it can be customized by the customers. In order to increase productivity and quality production, the company trying to develop business by adding some machines with the latest type and technologies.  Based on direct observations, Company produced a lot of defects and causes a negative impact. The problem can be solved by 4 quality control methods (exist in seven tools method) check sheets, pareto diagrams, control charts, and fishbone diagrams. This method used to determine the root of problems related with the quality products.  Check sheet method analysis shown intensity categories of product defects with label “always”, “often” and “rarely”. Then, the analysis of pareto diagrams showing the most dominant types of defects, with the name “Loncat P / L” and “Ambrol”. Furthermore, the results of the control chart analysis show an uncontrolled status. Finally, it can be known that the problem causing product defects is quality of dirty raw materials, machine failure, labour fatigue, poor work methods and unhealthy environment. recommendations given by researchers to the company are further tighten SOP implementation, control and supervise workforce performance, workforce briefings, and pay attention to 5S work culture.